Understanding rating addiction: US courts and the origins of rating agencies' regulatory license (1900-1940) - Marc Flandreau; Joanna Kinga Sławatyniec (Graduate Institute of International and Development Studies, 2013)
This paper discusses the regulatory license view that reliance by regulators on the output of rating agencies in the 1930s caused the agencies to become a central part of the fabric of the US financial system. Exploring pre-1930 court records, we find evidence of a growing reliance on the agencies that pre-dates the regulatory moves of the 1930s. We argue that courts began using ratings as financial community produced norms of prudence, providing a novel interpretation of the emergence of rating in financial systems as a product of trustee law. We remark that this created a legal license problem, creating incentives and conflicts of interest not unlike those which modern observers usually associate with regulation in the subprime crisis.
Keywords: 330; Ratingagentur; Geschichte; Finanzmarktregulierung; USA